A thermofluid network-based methodology for integrated simulation of heat transfer and combustion in a pulverized coal-fired furnace - van Der Meer, Willem Arie (Department of Mechanical Engineering, 2021)
Coal-fired power plant boilers consist of several complex subsystems that all need to work together to ensure plant availability, efficiency and safety, while limiting emissions. Analysing this multi-objective problem requires a thermofluid process model that can simulate the water/steam cycle and the coal/air/flue gas cycle for steady-state and dynamic operational scenarios, in an integrated manner. The furnace flue gas side can be modelled using a suitable zero-dimensional model in a quasi-steady manner, but this will only provide an overall heat transfer rate and a single gas temperature. When more detail is required, CFD is the tool of choice. However, the solution times can be prohibitive. A need therefore exists for a computationally efficient model that captures the three-dimensional radiation effects, flue gas exit temperature profile, carbon burnout and O2 and CO2 concentrations, while integrated with the steam side process model for dynamic simulations. A thermofluid network-based methodology is proposed that combines the zonal method to model the radiation heat transfer in three dimensions with a one-dimensional burnout model for the heat generation, together with characteristic flow maps for the mass transfer. Direct exchange areas are calculated using a discrete numerical integration approximation together with a suitable smoothing technique. Models of Leckner and Yin are applied to determine the gas and particle radiation properties, respectively. For the heat sources the burnout model developed by the British Coal Utilisation Research Association is employed and the advection terms of the mass flow are accounted for by superimposing a mass flow map that is generated via an isothermal CFD solution. The model was first validated by comparing it with empirical data and other numerical models applied to the IFRF single-burner furnace. The full scale furnace model was then calibrated and validated via detailed CFD results for a wall-fired furnace operating at full load. The model was shown to scale well to other load conditions and real plant measurements. Consistent results were obtained for sensitivity studies involving coal quality, particle size distribution, furnace fouling and burner operating modes. The ability to do co-simulation with a steam-side process model in Flownex® was successfully demonstrated for steady-state and dynamic simulations.